Effects of Incubation Temperature and Relative Humidity on Embryonic Development in Eggs of Red-Winged Tinamou (Rhynchotus rufescens). - Boleli, Isabel Cristina; de Queiroz, Sandra Aidar (My University, 2012)
This study was conducted to assess the effects of incubation temperature (34 C, 36[degree]C and 38[degree]C) and relative humidity (RH, 50% and 60%) on egg weight loss, embryo mortality, hatchability, incubation time and chick weight in eggs from red-winged tinamou. The eggs were placed in incubators that were operated at 34[degree]C, 36[degree]C, or 38[degree]C and 50% or 60% RH (mean wet bulb temperatures of 28[degree]C and 30[degree]C, respectively) from day 1 to hatching. Each treatment had two replicate groups of 30 eggs each. Hatchability varied with incubation temperature and RH and was highest for eggs incubated at 36[degree]C and 60% RH and lowest for eggs incubated at 38[degree]C. Early, intermediate and late embryo mortality were highest at 38[degree]C, 38[degree]C/50% RH, and 50% RH, respectively. Incubation period was longest at 34[degree]C and shortest at 38[degree]C/50% RH. Present results show the highest hatchability of red-winged tinamou eggs after incubation at 36[degree]C and 60% RH; highest embryo sensitivity to high temperature in the early period of incubation (1 to 7 days), to high temperature and low RH in the second period of incubation (8-14 days) and to low RH in the late period of incubation (after 15 days) and shortest incubation period with increasing temperature and RH.